If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 3x + 9 = 23 Reorder the terms: 9 + 3x = 23 Solving 9 + 3x = 23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 3x = 23 + -9 Combine like terms: 9 + -9 = 0 0 + 3x = 23 + -9 3x = 23 + -9 Combine like terms: 23 + -9 = 14 3x = 14 Divide each side by '3'. x = 4.666666667 Simplifying x = 4.666666667

| .08+.06(x+12)=7.72 | | (22b-7)-7(3b+4)=-5 | | 4x+3y-2xy=8 | | 13+b=23 | | 3t+9=24 | | 2+7v=79 | | 5n-9=16 | | 9p-7=11 | | 9p-7=11 | | 2x+78+7x+8=180 | | -0.25x^5+2.5x^3-6.25x= | | 3x^3+2x-4x^2= | | 9-x+5=8 | | 4x^2-9x-63=0 | | -1.25x^4+7.5x^2-6.25= | | 5x+3+6x-(4x*3)=21-5x | | 4(x+3)=x+3(x+4) | | x^2-3x+1=4-2x | | 17x+56=-12 | | (7w+5f)(7w-5f)= | | (7w+5f)*(7w-5f)= | | 6+2=48 | | 7+4=77 | | 24=52+n | | -204=m-41 | | 11=c+48 | | P+3.4=4.4 | | 1.76=a-2.94 | | -4+x=8 | | 0.5x^2-2= | | -2=b+(-4) | | 2+x-4=12 | | D+6(3)=-11 | | 2x-9=89 | | 1x-2=7 | | 23-56=x | | .2x+3.4+.8x=4 | | 234-45=2d-90d | | 234=x | | x^6+2x^3-3=0 | | 9x+8+7x=34+3x | | 3(8t+13)=303 | | 4(x)+9= | | 2x-10=x | | 23w=x | | 23w=x-fg-we | | x+(x+50)+y=180 | | 8n+3=6n+9 | | 3z=45 | | (2sin^2x)+(3sinx)+1=0 | | C+5=26-2C | | 14V+5-5V=4(V+5) | | 30x+90=90 | | 23x+78=x | | 1x-5=10 | | 10X+11y=11 | | 45-90+x=90 | | 59+32x=74-2x | | 4x=3(21-x) | | 2x+7=0 | | 2x+8=28 | | 3a-1=53 | | -15+4x=1 | | (-2)+(-7)= | | 40+34x=235x+90 |